Drainage Patterns and River Sinuosity in Padang, West Sumatra - Muhammad Fawzy Ismullah Massinai; Muhammad Altin Massinai; Hasanuddin Hasanuddin; Dewi Shafira (SCEJ (Shell Civil Engineering Journal), 2022)
Padang City is the capital of West Sumatra Province. This city has several rivers, each of which is a watershed. Watershed management can be done through geomorphological analysis by taking a landscape approach to finding out the tectonics working in the area. The morphotectonic analysis carried out in this study was an analysis of the drainage pattern and the river's sinuosity. The purpose of this study was to determine the characteristics of the watershed in the Padang City associated with tectonic activity based on morphometric analysis. The parameters used are the drainage pattern and the river sinuosity index. The results of the research that has been carried out, it is found that the genetic types of rivers found in the Padang City, West Sumatra are dendritic, trellis, and parallel types. Meanwhile, after analyzing the average value of the sinuosity index on river flows in Padang City, it was obtained a value of 1.56 or categorized as a meandering river type with active tectonics. The results of this study can be used as new information in watershed management in Padang City, West Sumatra Province.